Wavelet frames, Bergman spaces and Fourier transforms of Laguerre functions - Abreu, Luís Daniel (2006)
The Fourier transforms of Laguerre functions play the same canonical role in Wavelet analysis as do the Hermite functions in Gabor analysis. We will use them as mother wavelets in a similar way as the Hermite functions were recently used as windows in Gabor frames by Gr¨ochenig and Lyubarskii. Using results due to K. Seip concerning lattice sampling sequences on weighted Bergman spaces, we find a sufficient condition for the discretization of the resulting wavelet transform to be a frame. As in Gr¨ochenig-Lyubarskii theorem, the density increases with n, when considering frames generated by translations and dilations of the Fourier transform of the nth Laguerre function.